Kinetic and TL glow curve analysis of UV-, β- and γ-irradiated natural limestone collected from Chunkatta mines. Issue 11 (2nd December 2017) - Dubey, Vikas; Kaur, Jagjeet; Dubey, Neha; Pandey, Manoj Kumar; Suryanarayana, N. S.; Murthy, K. V. R.
ABSTRACT: Herein the manuscript reports kinetics and Thermoluminescence (TL) glow curve analysis of UV-, β- and γ-irradiated natural limestone samples collected from Chunkatta mines of Chhattisgarh basin. The collected samples were annealed at 100°C for 1 h for preheat treatment before irradiation after that the samples were irradiated by UV, β and γ, respectively. After irradiation the 1 mg weigh samples perform for TL glow curve analysis. Collected limestone was characterized by X-ray diffraction analysis technique and crystallite size was calculated using Scherer's formula. UV-irradiated sample shows the high-temperature peak centered at 250°C, for β-irradiated sample showed well resolved broad TL glow curve at 404 K which is fitted using computerized glow curve deconvolution (CGCD) technique. Similarly, for γ-irradiation the well resolved three distinct peaks at 209, 288 and 388°C showed the formation of deep trapping for γ-irradiation. Dose rate effect for UV- and γ-irradiation reported in details as well as the trap formation were described by trap depth model. Kinetic parameters for UV-, β- and γ-irradiation were calculated using peak shape method by CGCD technique. The study was determined the trap level formation and application related to TL dose response in collected limestone sample.